2014
DOI: 10.1371/journal.pone.0114632
|View full text |Cite|
|
Sign up to set email alerts
|

High-Throughput Genome Editing and Phenotyping Facilitated by High Resolution Melting Curve Analysis

Abstract: With the goal to generate and characterize the phenotypes of null alleles in all genes within an organism and the recent advances in custom nucleases, genome editing limitations have moved from mutation generation to mutation detection. We previously demonstrated that High Resolution Melting (HRM) analysis is a rapid and efficient means of genotyping known zebrafish mutants. Here we establish optimized conditions for HRM based detection of novel mutant alleles. Using these conditions, we demonstrate that HRM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 41 publications
1
82
0
Order By: Relevance
“…The prevalence of other common deletions suggested that the NHEJ repair is not random. Inspection of the DSB-flanking sequences suggested that the most frequent alleles may result from microhomology-mediated repair ( Figure S1), supporting previous reports (Wang et al 2013;Thomas et al 2014).…”
Section: Inactivation Of Insra and Insrb Impairs Glucose Metabolismsupporting
confidence: 86%
“…The prevalence of other common deletions suggested that the NHEJ repair is not random. Inspection of the DSB-flanking sequences suggested that the most frequent alleles may result from microhomology-mediated repair ( Figure S1), supporting previous reports (Wang et al 2013;Thomas et al 2014).…”
Section: Inactivation Of Insra and Insrb Impairs Glucose Metabolismsupporting
confidence: 86%
“…mRNA for the left and right TALENs was generated in vitro and injected into type AB zebrafish larvae at the one-cell stage. This founder generation (F0) was raised to adulthood and screened for the presence of SULT4A1 mutations by HRMA (Parant et al, 2009;Dahlem et al, 2012;Thomas et al, 2014). Mutants in this founder generation were chimeric with the potential for multiple mutations.…”
Section: Resultsmentioning
confidence: 99%
“…TALENs were designed to target the zebrafish SULT4A1 gene. SULT4A1 gene exon sequences (GenBank accession number NP_001035334) were analyzed for potential TALEN targeting sites using the Old TALEN Targeter program at https://tale-nt.cac.cornell.edu/ node/add/talen-old (Cermak et al, 2011;Doyle et al, 2012;Thomas et al, 2014). TALEN targeting sites within the second exon were chosen with the following parameters: left target sequence, 59-ATTGATGAGCAGCTTCCAGT-39; left repeat array sequence, NI, NG, NG, NN, NI, NG, NN, NI, NN, HD, NI, NN, HD, NG, NG, HD, HD, NI, NN, NG; right target sequence, 59-AGCCGG-GATTGGAGATTATCC-39; right repeat array sequence, NN, NN, NI, NG, NI, NI, NG, HD, NG, HD, HD, NI, NI, NG, HD, HD, HD, NN, NN, HD; spacer length, 14 nucleotides.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HRMA measures the decrease of fluorescence as double-stranded DNA denatures into single-stranded DNA, producing sequencespecific melting profiles that are dependent on amplicon lengths and GC content (18 -20 ). Because the 2 alleles of each DIP have substantial sequence differences, small biallelic DIPs are attractive candidates for genotyping by HRMA (13,21,22 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%